Análise do secretoma de bactérias isoladas do alimento de larvas de abelhas brasileiras sem ferrão em Drosophila melanogaster modelo para Doença de Alzheimer - Rodrigues, Tamiris Sabrina (2021)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized by the presence of amyloid plaques, neurofibrillary tangles, inflammation, oxidative damage, synapse loss, and selective neuron death. Inhibition of BACE1 expression has been considered a therapeutic target for the prevention and treatment of Alzheimer's disease. This study evaluated BACE1 inhibitory activity of secretome of bacteria isolated from stingless bees’ larval food of native Brazilian species, Melipona quadrifasciata and Tetragonisca angustula. For this purpose, the screening of secretomes in the Drosophila melanogaster transgenic strains, followed by in silico analysis. We assessed the survival rate of transgenic fly with rough eye phenotype, generated by overexpression of human APP and BACE1 orthologs in the developing nervous system of the eye. Morphological modifications in the eyes of newly hatched D. melanogaster were examined. We verified reduction of morphological alterations in the eye, presenting compound eyes with smooth surface, difference in the fusion of the omatids and presence of a large number of bristles, in the groups treated with the S9 and S27 secretomes when compared to the control groups. Histological sections showed agreement with this improvement, exhibiting compound eyes with regular morphology and organized surface. The anti-AD model of D. melanogaster was treated with several bacterial secretomes for 15 days after hatching. The flies treated with the S1 secretome showed an improvement in the climbing rate when compared to the negative control and vehicle groups. Additionally, the groups treated with the S1 and S27 secretomes showed a decline in beta-amyloid levels after 15 days of treatment. The histology analysis of the brain revealed a decrease in neurodegeneration in flies treated with S1 visualized through the reduction of vacuolar lesions, when compared to the negative control and vehicle groups. We carried out the proteomic analysis of the most efficient secretomes in the tests with D. melanogaster. The in silico analysis selected the most potentially bioactive peptides to interact with BACE1 and beta-amyloid, predicting the docking between them. Our analysis found four peptides that interact with BACE1 and β-amyloid plaques, with potential action in reducing the neurodegenerative process. Thus, our investigations resulted in the identification of potentially bioactive peptides that can serve as a prototype for new drugs for the prevention or treatment of Alzheimer's Disease. The secretome of bacteria isolated of the larval food of stingless bees proved to be a potential source of therapeutic molecules targeting neurodegenerative disorders.